Money and prices in models of bounded rationality in high inflation economies - Albert Marcet; Juan Pablo Nicolini (European Central Bank (ECB), 2005)
This paper studies the short run correlation of inflation and money growth. We study whether a model of learning does better or worse than a model of rational expectations, and we focus our study on countries of high inflation. We take the money process as an exogenous variable, estimated from the data through a switching regime process. We find that the rational expectations model and the model of learning both offer very good explanations for the joint behavior of money and prices.
Keywords: D83; E17; E31; 330; Inflation andmoney growth; quasi-rationality; switching regimes; Begrenzte Rationalität; Inflation; Geldnachfrage; Rationale Erwartung; Schätzung; Lateinamerika